The search for the ideal tendon repair in zone 2: strand number, anchor points and suture thickness. (January 2014) - Savage, R.
This review article examines the mechanical factors involved in tendon repair by sutures. The repair strength, repair stiffness and gap resistance can be increased by increasing the number of core strands and anchor points, by increased anchor point efficiency and the use of peripheral sutures, and by using thicker sutures. In the future, laboratory tests could be standardized to a specific animal model and to a defined cyclic motion programme. Clinical studies support the use of multi-strand core and peripheral sutures, but two-strand core sutures are not adequate to ensure consistently good clinical results. Training surgeons in complex tendon repair techniques is essential.